ANALISIS KESALAHAN EJAAN BAHASA INDONESIA PADA PENULISAN WACANA DESKRIPSI SISWA SMA NEGERI 1 DOLOK BATU NANGGAR - Pratiwi, Siska; Kartolo, Rahmat (Jurnal Bahastra, 2023)
Indonesian always grows and develops according to changing times and technological advances. As a language that experiences growth and development, of course there are many obstacles in the process, one of which is related to the spelling used. Even though the use of language spelling has been applied in written communication for a very long time, in practice there are still many errors in writing. The purpose of this study was to analyze Indonesian spelling errors in the discourse descriptions of class XI students at SMA Negeri 1 Dolok Batu Nanggar, Simalungun Regency. This research was conducted using a qualitative approach which is included in linguistic research which aims to produce descriptive data. The instrument used to capture data in this study was observation to analyze EBI errors in student-made descriptive discourse. Data analysis in this study began with data collection through observation and documentation, then identification, description, and classification of data based on errors were carried out. Based on the results of an analysis of the students' discourse descriptions, several mistakes were made by students, including errors in the use of letters, errors in the use of capital and lowercase letters, errors in writing prepositions and affixes, errors in writing loanwords and errors in the use of punctuation marks. The most dominant error is an error in writing absorption words, namely with a completeness of 59.72% which is far from sufficient.